Significance of determination of hemodynamic phenotypes in early diagnosis of cardiovascular disorders in children with diabetes mellitus - H. O. Lezhenko; O. Ye. Pashkova; K. V. Samoilyk (Zaporozhye State Medical University, 2021)
Aim. To stratify hemodynamic phenotypes in children with diabetes mellitus and their frequency, depending on the duration of the disease. Materials and methods. The study involved 72 children suffering from diabetes, aged 10 to 16 years who were divided into 3 groups. The first group - 22 children with diabetes mellitus up to 1 year. The second group - 24 patients with a disease duration of 1 to 5 years. The third group - 26 children with the disease over 5 years. Control group - 20 children, representative by age and sex. All children underwent daily blood pressure monitoring (ABPM) with the ABPM-04 device (Meditech Ltd, Hungary). Diagnosis of latent hemodynamic disorders was performed by the method of quantitative analysis of the relationships of blood pressure parameters, which involved a linear regression of systolic blood pressure by pulse blood pressure. According to the results of regression, 6 hemodynamic phenotypes were determined, which characterized the individual features of the circulatory system: harmonic, myocardial-insufficient subtype of harmonic, borderline diastolic harmonic, borderline systolic harmonic, dysfunctional diastolic and dysfunctional systolic. According to ABPM results, the ambulatory arterial stiffness index (AASI) was calculated using a linear regression equation. The results were statistically processed using statistics software package Statistica 13.0 (StatSoft Inc., No. JPZ8041382130ARCN10-J). Results. It was found that in the dynamics of diabetes the registration of the harmonic hemodynamic phenotype during the day decreased due to an increase in the proportion of patients with dysfunctional diastolic hemodynamic phenotype. At the same time, in children with diabetes, there was a significant increase in AASI from the first year of the disease with a progressive increase with its dynamics. The highest values of AASI were observed in dysfunctional hemodynamic phenotype. Conclusions. In children with diabetes mellitus observed the formation of disharmonious hemodynamic phenotypes in the dynamics of the disease. In combination with increased vascular stiffness these changes realized in systemic circulatory disorders and the development of a diabetic angiopathy. Detected disorders, apparently, became the risk factors of hypertension. Determination of hemodynamic phenotype in children with diabetes mellitus can be used as screening method for preclinical diagnosis of latent disorders of the cardiovascular system, early treatment and prevention.